2021
DOI: 10.3390/nu13030782
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Effect of Caffeine on Substrate Oxidation during Exercise

Abstract: By using deceptive experiments in which participants are informed that they received caffeine when, in fact, they received an inert substance (i.e., placebo), several investigations have demonstrated that exercise performance can be enhanced to a similar degree as a known caffeine dose. This ‘placebo effect’ phenomenon may be part of the mechanisms explaining caffeine’s ergogenicity in exercise. However, there is no study that has established whether the placebo effect of caffeine is also present for other ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It is suggested that future studies pay more attention to the interaction of CYP1A2 genotype and caffeine ergogenic responses. It should be noted that the present study compared the effects of caffeine only with the placebo, while it has been shown that placebos have had ergogenic effects on performance compared with control conditions [ 64 , 65 , 66 , 67 ]. It is possible that due to the limitation of the present study design (lack of control conditions), the significant effects of caffeine on handgrip strength or upper-body explosive power are hidden compared with the control conditions.…”
Section: Discussionmentioning
confidence: 96%
“…It is suggested that future studies pay more attention to the interaction of CYP1A2 genotype and caffeine ergogenic responses. It should be noted that the present study compared the effects of caffeine only with the placebo, while it has been shown that placebos have had ergogenic effects on performance compared with control conditions [ 64 , 65 , 66 , 67 ]. It is possible that due to the limitation of the present study design (lack of control conditions), the significant effects of caffeine on handgrip strength or upper-body explosive power are hidden compared with the control conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the improvement of FIET and vertical jump performance may be partly due to placebo ergogenic effects. Some previous studies have also confirmed that the ergogenic or physiological effect of the placebo can be comparable to caffeine [ 44–47 ], but others have not reported a significant effect [ 48 ]. Using deceptive interventions, it has also been reported that a placebo enhanced performance when participants were informed that the substance they were consuming was caffeine [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Placebo effect is a phenomenon that occurs when an inert substance is given instead an active medication, but individuals are convinced that they had received the active substance. 27 Environmental and psychosocial determinants are two main factors for the placebo effect . 28 These two factors also include conditioning, verbal suggestions, and habits of health workers (in this case researchers).…”
Section: Discussionmentioning
confidence: 99%